NEEDS ANALYSIS OF THE RELATIONSHIP BETWEEN UNIFORM PERCEPTION AND ORGANIZATIONAL PRIDE AND JOB SATISFACTION AMONG POLICE OFFICERS - Razali Alias, Mohd; Bahron, Arsiah; Lambin, Regina (International Journal of Psychosocial Rehabilitation, 2020)
The Royal Malaysian Police (PDRM) System is an entity that has a standardized or centralized system whereby it is the main national security institution in preserving national security, especially in matters related to national security and peace. In the early '80s, police officers were highly respected individuals, diligent and earnest in carrying out their duties, maintaining public order, and keeping the community safe and secure. However, the study of job satisfaction related to the uniform perception and organizational pride has received little attention from the context of the country's main security force, the Royal Malaysian Police. The purpose of this study therefore was to detect the direct and indirect connection between the uniform variable of perception and the organizational pride variable in the satisfaction of work among police officers of past scholars.This study is based on the theory of job satisfaction selected by adding the value of the relationship between uniform perception and organizational pride as independent variables among Sabah contingent police officers. At the end of this study, we should present the most recent models which can be applied to improve efficiency and organizational morale as well as to maximize community productivity. The findings of this study will be used to assist in assessing future interventions and team policies.